Translation of collocations in the Qur'an - Alhalawani, Ali Alsayed Hassan (IIUM Press, International Islamic University Malaysia, 2017)
Generally, lexical collocation has become an increasingly important linguistic phenomenon in the fields of learning second languages as well as translation. Lexical collocation has been viewed by some linguists as a ‘problem’ (Ivir 1988), by others as a ‘phenomenon’ (Hoogland 1993) and yet by others as a ‘lexical relation’ (Emery 1991). Firth (1957) expects mutual expectancy between collocated words, but the rule or nature of such expectancy may not be precisely known. This rule might be contextual, grammatical, or semantic. Careful analysis of Arabic collocations may add more weight to the argument that collocation is more of a semantic relation than anything else. Besides, as is stated by (Emery 1987), collocational relations may differ in terms of combinability from one language to another.The present book draws attention to this “phenomenon” in the field of Arabic studies in an attempt to provide a more precise definition, description and classification thereof. This is due to its great importance in terms of learning Arabic as a second language as well as translation from Arabic into English and vice versa. The study will also explore the strategies adopted for rendering lexical collocations from Arabic into English in an endeavor to reach the best possible strategy in this respect. It also tries to extract a model of lexical collocation from the Qur’an (the Sacred Book of Islam), and analyze it using the corpus made available to me which comprises about 5.000.000 words. The selected collocation for the study is iqamat al-salah due to the importance this Act of Worship has as far Islam is concerned. I will adopt a comparative methodology in tackling the linguistic phenomenon to be examined here in order to differentiate between the nature of collocation in both Arabic and English.